2021
DOI: 10.3390/children8100884
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cardiometabolic Risk Factors in School-Aged Children with Excess Body Weight in the Al Ain City, United Arab Emirates: A Cross-Sectional Study

Abstract: (1) Background: This study aimed to examine the distribution of cardiometabolic risk factors (CMRF) in school-aged children with excess body weight (overweight and obese) in Al Ain City, United Arab Emirates and identify the factors associated with increased cardiovascular risk factors between boys and girls. (2) Methods: A cross-sectional survey of children aged 6–17 years was conducted in Al Ain from 1 August 2019 to 31 December 2020. Binary logistic regression analysis was performed to investigate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The average of these three measurements was registered. 12 The body fat composition, and electrical impedance or BF% using the Tanita Body composition analyzer TBF-300. Tanita was used to determine body composition, including BF, body fat mass (BFM) (kg), fat-free mass (FFM), body muscle mass (BMM), and total body water (TBW).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average of these three measurements was registered. 12 The body fat composition, and electrical impedance or BF% using the Tanita Body composition analyzer TBF-300. Tanita was used to determine body composition, including BF, body fat mass (BFM) (kg), fat-free mass (FFM), body muscle mass (BMM), and total body water (TBW).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this metabolic derangement is probably due to a family history of obesity, an unhealthy diet, and an inactive lifestyle. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity among adults is rapidly increasing in the developing world, including the Gulf region [ 5 ]. Moreover, cardiometabolic risk factors (CMRFs) are more prevalent among children and youth who are overweight or obese than those with a healthy weight [ 6 , 7 ]. Previous studies have affirmed that the prevalence of cardiovascular risk factors in childhood has increased, and biomarkers of adverse cardiovascular outcomes have already been found in childhood with obesity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our recently published study [ 7 ], we reported that the prevalence of CMRF in children, such as high levels of triglycerides, total cholesterol, and glucose, was quite high in Emirati school-aged children with excess body weight. This may be because of the consumption of unhealthy food, a sedentary lifestyle, and family history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation